2010
DOI: 10.1002/biot.200900233
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time PCR‐based determination of gene copy numbers in Pichia pastoris

Abstract: Pichia pastoris is a preferred host for heterologous protein production. Expression cassettes are usually integrated into the genome of this methylotrophic yeast. This manuscript describes a method for fast and reliable gene copy number determinations for P. pastoris expression strains. We believe that gene copy number determinations are important for all researchers working with P. pastoris and also many other research groups using similar gene integration techniques for the transformation of other yeasts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…10% (0.61% Ϯ 0.07%). The expected CN of 1 was slightly underestimated, but variation to this extent was also noted with quantitative PCR (qPCR) (48) CN determinations in P. pastoris (43,49,50). Also, relative conclusions on the CN differences between the strains were not influenced.…”
Section: Effect Of Cn Variations Snps and Insertions And Deletions mentioning
confidence: 91%
“…10% (0.61% Ϯ 0.07%). The expected CN of 1 was slightly underestimated, but variation to this extent was also noted with quantitative PCR (qPCR) (48) CN determinations in P. pastoris (43,49,50). Also, relative conclusions on the CN differences between the strains were not influenced.…”
Section: Effect Of Cn Variations Snps and Insertions And Deletions mentioning
confidence: 91%
“…The GS115 yeast cells were then cultured on MM (1.34% YNB, 4 ϫ 10 Ϫ5 % biotin, 0.5% methanol, and 1.5% agarose) and MD (1.34% YNB, 4 ϫ 10 Ϫ5 % biotin, 2% dextrose, 1.5% agarose) plates for distinguishing the His ϩ Mut ϩ from His ϩ Mut s transformants. After isolation of genomic DNA from the His ϩ Mut ϩ GS115 transformants, real-time PCR was performed with species-specific primers (Table 3) to measure the gene copy number of Pept1 cDNA in yeast cells (Abad et al, 2010). The ARG4 gene of yeast was set as the internal control, and the plasmid DNA pPIC3.5K/Pept1 was set as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Two strains thought to feature single and multicopy gene integration events were chosen and are henceforth named RgDAO_sc and RgDAO_mc, respectively. Quantitative real-time PCR analysis (Abad et al 2010a) confirmed the presence of 1 (RgDAO_sc) and 12-13 (RgDAO_mc) copies of the expression cassette integrated in the P. pastoris genome.…”
Section: Expression Designmentioning
confidence: 93%
“…After electroporation and regeneration for 2 h at 30°C using agitation at 60 rpm, aliquots (0.2 ml) were plated on solid selection medium containing 100 mg Zeocin/l. The number of copies of RgDAO expression cassettes integrated into the P. pastoris genome was determined by quantitative real-time PCR as described in Abad et al (2010a), employing the AOX1 promoter as target and the endogenous ARG4 gene as a reference.…”
Section: Construction Of P Pastoris Expression Cassettesmentioning
confidence: 99%